Adverse Association within Epilepsy and Cardiovascular Events - Masood-Uz-Zaman, Fahim Ahmed Soomro, Faraz Ahmed, Sajjad Hussain Jalbani, Majid Ali Khand, Sunil Dat Maheshmari (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the association of epilepsy and cardiovascular event. Study Design: Case control retrospective study Place and Duration of Study: Department of Neurology, Isra University, Hyderabad from 1st September 2022 to 31st August 2023. Methodology: Seven hundred cases were enrolled wherein 350 epileptic patients and 350 control cases. The study focused on epileptic patients within the age >18 years who were identified from hospital records. Those patients who suffered from epilepsy were placed in group 1 while those having no epilepsy and considered as controls were placed in group 2. The complete information in context to the medication code carbamazepine, valproate, lamotrigine used, was also recorded and compared within group 1 cases. Results: Hypertension appeared to be the leading factor followed by poor nutrition and diabetes mellitus. All the cardiovascular outcomes including ischemic stroke, heart failure MI were also significantly higher in number as compared to control group. Conclusion: Incidence rate and prevalence of cardiovascular events were significantly higher in hospitalized patients of epilepsy. Keywords: Cardiovascular events, Seizures, Epilepsy, Mortality